World commodity outlook 1984 : industrial raw materials - The Ecoomist Intelligence Unit; Export of goods (London : Economist Intelligence Unit Ltd, 1984)
This paper highlights that there have been increasing signs of hesitancy in the pace of world economic expansion in the first half of 1985. In the United States, output growth declined to an average of 1 percent (at an annual rate) in the first two quarters of the year from 5.7 percent during 1984, and in other industrial countries, the pace of recovery was also generally subdued. Commodity prices fell significantly, thus weakening growth prospects in many developing countries.
aia 04/04/2019
Loans
Keywords: Economics; Exporting countries; Exporters